2013
DOI: 10.1039/c3nr04185a
|View full text |Cite
|
Sign up to set email alerts
|

Sol-hydrothermal synthesis and optical properties of Eu3+, Tb3+-codoped one-dimensional strontium germanate full color nano-phosphors

Abstract: Novel near-UV and blue excited Eu(3+), Tb(3+)-codoped one dimensional strontium germanate full-color nano-phosphors have been successfully synthesized by a simple sol-hydrothermal method. The morphologies, internal structures, chemical constitution and optical properties of the resulting samples were characterized using FE-SEM, TEM, HRTEM, EDS, XRD, FTIR, XPS, PL and PLE spectroscopy and luminescence decay curves. The results suggested that the obtained Eu(3+), Tb(3+)-codoped strontium germanate nanowires are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…Previously, Lin et al successfully synthesized novel near-UV and blue-excited Eu 3+ , Tb 3+ -co-doped one-dimensional strontium germanate full-color nanophosphors by a simple sol-hydrothermal method. They found that incorporation of the Eu 3+ and Tb 3+ ions into strontium germanate resulted in a slight shrinkage of the lattice constants and the unit cell volume because Eu 3+ and Tb 3+ had smaller radii than Sr 2+ , indicating the Eu 3+ and Tb 3+ ions had been incorporated into the host lattice of SrGe 4 O 9 and did not change the crystal structure [24]. Those results also suggested that the Eu 3+ ions substituted into the sites of Sr 2+ ions.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Previously, Lin et al successfully synthesized novel near-UV and blue-excited Eu 3+ , Tb 3+ -co-doped one-dimensional strontium germanate full-color nanophosphors by a simple sol-hydrothermal method. They found that incorporation of the Eu 3+ and Tb 3+ ions into strontium germanate resulted in a slight shrinkage of the lattice constants and the unit cell volume because Eu 3+ and Tb 3+ had smaller radii than Sr 2+ , indicating the Eu 3+ and Tb 3+ ions had been incorporated into the host lattice of SrGe 4 O 9 and did not change the crystal structure [24]. Those results also suggested that the Eu 3+ ions substituted into the sites of Sr 2+ ions.…”
Section: Resultssupporting
confidence: 53%
“…When the synthesizing temperature was 1200 °C, the emission intensity of the transition of 5 D0-7 F2 (616 nm) for Sr1.9Eu0.1ZnMoO6 and Sr1.88Eu0.12ZnMoO6 phosphors was higher than that of 5 D0-7 F1 (597 nm), as Figure 4 shows. The transitions of 5 D0-7 F1 (588 nm), 5 D0-7 F2 (612 nm), 5 D0-7 F3 (649 nm), and 5 D0-7 F4 (695 nm) for the Eu 3+ ions can be simultaneously observed in the emission spectrum of the Eu 3+ , Tb 3+ -co-doped one-dimensional strontium germinate, full-color nano-phosphors [24]. However, introduction of the Eu 3+ ions in the Sr2−xEuxZnMoO6 lattice results in disorder.…”
Section: Rose the Results Inmentioning
confidence: 91%
See 1 more Smart Citation
“…The 0.1 M KCl solution was prepared from potassium chloride and deionized water. Li doped bismuth oxide nanorods were synthesized by the hydrothermal process which was similar to that reported by Lin et al 25 Briefly, sodium bismuthate and lithium acetate with the mass ratio of 21:5 were mixed with 60 mL deionized water at room temperature with magnetic stiring for 0.5 h. Then the mixtures with lithium acetate and sodium bismuthate were transferred into a Teflon-lined stainless autoclave. The stainless autoclave was sealed and heated to 80-180 ºC and maintained for 0.5 h to 24 h. The white precipitates were gained by the centrifugation, washed using deionized water for several times.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrothermal route is an effective method for the synthesis of doped one-dimensional (1D) nanoscale materi-als [14][15][16][17]. In the paper, Ce doped germanium dioxide nanowires have been synthesized by the hydrothermal route using germanium dioxide and Ce acetate as the raw materials, sodium dodecyl sulfate (SDS) as the surfactant.…”
Section: Introductionmentioning
confidence: 99%